APRIORI ALGORITHM FOR DETERMINING THE DEMAND LEVEL OF STATIONARY PT. MAIN GAFA INDONESIA - Sri Wahyuni; Wulan Dari; Lusa Indah Prahartiwi (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2021)
PT Gafa Utama Indonesia is one company that provides services in teaching and writing. Until now, PT Gafa Utama Indonesia already has 30 well-known branches in Jabodetabek. In the teaching and learning process, Gafa needs some stationery and teaching aids. The high demand for office stationery, and the mismatch of inventory in the warehouse, affects the fluency in the teaching and learning process. The data used in this study is the report data on the demand for office stationery for the period January-December 2018. This study uses a priori algorithm method and assessment with tanagra tools. The results of manual calculations with Microsoft Excel are the same as those using the tanagra tool. The final result shows the 2 items with the most demand, namely an eraser and a sharpener with at least 50% support, and 50% confidence. These results can be used as a reference for PT Gafa Utama Indonesia in the supply of office stationery